Water and salt transport properties of the cellulose triacetate/reduced graphene oxide nanocomposite membranes. (1st December 2020) - You, Meng; Wang, Binfei; Singh, Paramjit; Meng, Jianqiang
Abstract: The relationship between desalting membrane and its water/salt transport properties remain largely unknown. This is especially true for polyamide thin film nanocomposite (TFN) membranes which have shown excellent desalination performance and attracted booming attention in recent years. Considering cellulose triacetate (CTA) can be made into dense membranes whose transport properties can be measured based on the solution-diffusion theory, we systematically study the water/salt transport property of the CTA nanocomposite membranes blended with reduced graphene oxide (rGO) of varying reduction degrees, with multilayer graphene oxide (MGO) and single layer graphene oxide (SGO) as control samples. The nanocomposite membranes show enhanced membrane density and glass transition temperature (Tg ) due to the interaction of the polar group in GO/rGO with CTA chains. The GO (rGO) frustrates the polymer chain packing and decreases crystallinity of CTA membrane. The adding of rGO increases the water permeability by increasing its diffusivity due to the decreased crystallinity and additional channel from (r)GO, but decreases the salt permeability by decreasing its diffusivity due to membrane densification and the interactions of ions with GO/rGO. The water permeability and diffusivity of the nanocomposites increase when its water sorption decreases, which is against the trend of pure polymers, presumably due to the fact that water sorption is not a good reflection of the free volume in this heterogeneous membrane. Meanwhile, the GO/rGO blending slightly increases water sorption without changing the salt sorption because the newly-introduced polar groups in GO/rGO traps water and suppress its solvation capacity for salt. Both the water permeability and the water/salt selectivity increase with the reduction degree due to the decreased water transport resistance. Graphical abstract: Image 1 Highlights: RGO of varying reduction degrees was prepared by hydrothermal reduction. Blending of rGO dramatically increases water diffusivity and permeability. Blending of rGO decreases salt diffusivity and permeability. Blending of rGO slightly increases water sorption without changing salt sorption. Both water permeability and water/salt selectivity increase with reduction degree.